2012
DOI: 10.1007/s00705-012-1459-8
|View full text |Cite
|
Sign up to set email alerts
|

Partial molecular characterization of different proviral strains of bovine leukemia virus

Abstract: Bovine leukemia virus (BLV)-infected cattle were classified by their proviral load into low and high proviral load profiles (LPL and HPL, respectively). Blood from these animals was used to infect sheep to obtain multiple identical copies of integrated provirus. An env fragment of BLV was amplified from all infected sheep and sequenced. The sequences that were obtained were compared to already published BLV genome sequence, resulting in three clusters. Mutations could not be attributed to the passage of provir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…None of the original wild BLV variants (Cow 485 or Cow 141) was recovered after the infection of the sheep and the rabbit, or replication in FLK and CC81 cells. In the past, the BLV env gene mutation rate was assumed to be low, even after the experimental passage of the provirus in vivo (Juliarena et al, 2013). Even though BLV has been shown to have lower genetic variation compared to other retroviruses (Price et al, 1998;Craigo et al, 2009), and to contain highly conserved regions involved in the cell-virus interaction (Coulston et al, 1990;Mamoun et al, 1990), our results support recent studies reporting about the genetic variation of BLV and the circulation of 7 genetic distinct groups (Zhao and Buehring, 2007;Moratorio et al, 2010), of which 4 were detected in Brazil (Camargos et al, 2002(Camargos et al, , 2007.…”
Section: Resultsmentioning
confidence: 99%
“…None of the original wild BLV variants (Cow 485 or Cow 141) was recovered after the infection of the sheep and the rabbit, or replication in FLK and CC81 cells. In the past, the BLV env gene mutation rate was assumed to be low, even after the experimental passage of the provirus in vivo (Juliarena et al, 2013). Even though BLV has been shown to have lower genetic variation compared to other retroviruses (Price et al, 1998;Craigo et al, 2009), and to contain highly conserved regions involved in the cell-virus interaction (Coulston et al, 1990;Mamoun et al, 1990), our results support recent studies reporting about the genetic variation of BLV and the circulation of 7 genetic distinct groups (Zhao and Buehring, 2007;Moratorio et al, 2010), of which 4 were detected in Brazil (Camargos et al, 2002(Camargos et al, , 2007.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, LTR region variability may contribute to viral transcription regulation, a process that is directly related to BLV virulence and pathogeny (Moratorio et al, 2013). In addition, small nucleotides polymorphisms identified in the LTR region may be responsible for the emergence of the 2 different infection profiles (Juliarena et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine leukemia virus (BLV) belongs to the family Retroviridae, and it is the causative agent of enzootic bovine leukosis (EBL) [7]. Although most countries in western Europe are EBL-free, BLV infection has a worldwide distribution and sero-epidemiological studies have reported high prevalence in some countries [1].…”
mentioning
confidence: 99%
“…Partial env and gag sequences have been used to reveal genetic variation and to characterize BLVs [7]. A recent phylogenetic study of the BLV env gene from strains isolated worldwide demonstrated that the virus can be divided into eight genotypes [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation